Income Growth in German Households: East Germany Falls Behind - Karl Brenke (Weekly Report, 2005)
Following the enormous growth in household incomes in the former East Germany during the first half of the 1990s (which was based, in particular, on meteoric wage rises, accompanying pension adjustments, and the increase in receipt of social welfare benefits), east German incomes subsequently expanded only moderately. Income growth was not as strong as in west Germany, largely because total earned income expanded only marginally. This feeble growth was due exclusively to the weak employment trend. While the income growth in households with an earned income was lower from the mid-1990s onward than it had been previously, it nonetheless kept pace with the trend for average earned income in west German working households. The adjustment of east German wages to the west German level continued, albeit at an increasingly slow pace. A growing number of east German households are dependent on social transfers, and these transfers account for an increasingly large share of household income. There is little evidence of a similar trend in west Germany, given that employment growth is somewhat more favorable in this part of the country. Moreover, the share of east German households in receipt of old-age pensions has increased at a stronger rate than in west Germany. In 2002, social security benefits and statutory pensions accounted for almost 40% of total net household income in east Germany, compared with only just over a quarter of net household income in west Germany. Not only has the share of pensioner households increased in east Germany - as it also has in the western part of the country - but the structure of households has also undergone a general transformation within a relatively short period of time. Shortly after reunification, east German households had more members than west German households, on average, whereas now they have fewer. In particular, the share of families with children has declined, while the share of single parents has remained unchanged. As a result of this decline in average household size, since the mid-1990s east Germany has fallen only slightly behind west Germany with respect to household income weighted by household composition.
Keywords: 330